Multidimensional Approach to Seasonal Respiratory Disorder - Bronchitis (Homoeopathy for All, 2025)
Cough is the most common illness related reason for ambulatory care visits for hospitals. Cold, chest discomfort and an irritating cough that may be lasting for weeks? If these symptoms sound familiar then you possibly have Bronchitis. This article review about causes, risk factors, different type, clinical presentation general management including some home remedies management and homoeopathic way of treatment of bronchitis. Homoeopathy treats the person as a whole. It means that homoeopathic treatment focuses on the patient as a person, as well as his pathological condition.
Keywords: ambulatory; Bronchitis; homoeopathic; pathological